2021
DOI: 10.1038/s41598-021-84850-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated ω-3 fatty acids inhibit ACE2-controlled SARS-CoV-2 binding and cellular entry

Abstract: The strain SARS-CoV-2, newly emerged in late 2019, has been identified as the cause of COVID-19 and the pandemic declared by WHO in early 2020. Although lipids have been shown to possess antiviral efficacy, little is currently known about lipid compounds with anti-SARS-CoV-2 binding and entry properties. To address this issue, we screened, overall, 17 polyunsaturated fatty acids, monounsaturated fatty acids and saturated fatty acids, as wells as lipid-soluble vitamins. In performing target-based ligand screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 36 publications
5
86
0
1
Order By: Relevance
“…SARS-CoV-2 spike-protein-expressing cells binding to soluble hACE2. To transduce cells with eGFP-luciferase-SARS-CoV-2 spike S1 lentivirus vector (GenScript, Piscataway, NJ), A549 cells, seeded into a 6-well plate in the presence of complete growth medium, were treated with 8 μl/ml polybrene (Sigma, St. Louis, MO) for 30 min., followed by the addition of eGFPluciferase-SARS-CoV-2 spike S1 lentivirus at MOI = 40 [51], and spin-inoculation at 1,000 x g. for 1.5h. After 24h at 37˚C incubation, cells were fed with fresh complete growth medium.…”
Section: Test Compounds Antibodies Recombinant Proteins and Inhibitorsmentioning
confidence: 99%
“…SARS-CoV-2 spike-protein-expressing cells binding to soluble hACE2. To transduce cells with eGFP-luciferase-SARS-CoV-2 spike S1 lentivirus vector (GenScript, Piscataway, NJ), A549 cells, seeded into a 6-well plate in the presence of complete growth medium, were treated with 8 μl/ml polybrene (Sigma, St. Louis, MO) for 30 min., followed by the addition of eGFPluciferase-SARS-CoV-2 spike S1 lentivirus at MOI = 40 [51], and spin-inoculation at 1,000 x g. for 1.5h. After 24h at 37˚C incubation, cells were fed with fresh complete growth medium.…”
Section: Test Compounds Antibodies Recombinant Proteins and Inhibitorsmentioning
confidence: 99%
“…A similar fatty acid binding pocket was also observed in SARS-CoV and MERS-CoV ( 40 ). It has also been reported that omega-3 fatty acids, including linoleic acid and eicosapentaenoic acid (EPA), can interact with the receptor binding domain of the SARS-CoV-2 S protein and inhibit attachment to the ACE2 receptor in vitro ( 41 ).…”
Section: Lipids In Viral Entrymentioning
confidence: 99%
“…To date, sparse evidence has implicated omega-3 fatty acids in the prevention and treatment of COVID-19 [ 106 , 107 ]. Nevertheless, it has been shown that the omega-3 PUFAs inactivate enveloped viruses like SARS-CoV2 and inhibit ACE2-mediated binding and cellular entry of SARS-CoV-2 [ 108 ]. Furthermore, beneficial reports of omega-3 PUFAs have been reported in patients with sepsis and sepsis-induced ARDS [ 109 , 110 ].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%